Análise das normativas sobre o modelo de cuidado voltado ao uso de substâncias psicoativas no Brasil - Silva, Lara Moreira de Oliveira (Universidade Federal de São Carlos, 2024)
In Brazil, the health care provided for the use of psychoactive substances is marked by aspects that differ in terms of the theoretical approach to the issue. On the one hand, there is the perspective of harm reduction, based on a model of care centered on the user and on the maintenance of their autonomy. On the other, there is the presence of assumptions associated with the abstinence approach, based on linking health care to equipment that promotes the social isolation of users, which compromises their rights as citizens and the prerogative of care in freedom, widely defended by the Brazilian Psychiatric Reform (RPB) and won as a constitutional right under Law 10.216/2001. In this way, this study was built on the qualitative method, of a theoretical nature, with the aim of analyzing national public health policies, seeking to identify the scope, limits and contradictions between approaches. To this end, a documentary analysis was carried out of the national mental health policy (PNSM), which, based on Ordinance No. 3.088/2011, establishes the Psychosocial Care Network (RAPS) within the scope of the Unified Health System (SUS), also taking into account the changes made to it between the date of its publication and 2022, the year in which the research began. The documents were subjected to thematic content analysis, resulting in 3 general categories of meaning: I. Reaches of the psychosocial paradigm; II. Limits to the psychosocial paradigm and; III. contradictions between approaches. Subsequently, these results were articulated in the discussion, which led to the conclusion that, although the model of care based on harm reduction is postulated as part of the psychosocial care model, and is therefore included in the regulations that guide the care offered in the RAPS devices, the incorporation of manicomial equipment has been present since its creation. In addition, it was also possible to glimpse the extent of the regression in psychosocial care brought about by the changes made to the policy, especially since Ordinance No. 3588/2017.
Analysis of regulations on the care model aimed at the use of psychoactive substances in Brazil
Keywords: Substâncias psicoativas; Redução de danos; Rede de atenção psicossocial; Política nacional de saúde mental; Psychoactive substances; Harm reduction; Psychosocial care network; National mental health policy; CIENCIAS HUMANAS::PSICOLOGIA